Evaluation Of Phenolic Compounds (Citrus sinensis) And Its Antioxidant Capacity (2021)
The main objective of this research is to evaluate the phenolic compounds extracted from the peel of the Valencia orange (Citrus. sinensis), this with the purpose of being applied in the meat industry as antioxidants, and its possible sensory acceptance, for which two different extraction methods were applied, being these the ultrasound and Soxhlet, using ethanol as solvent, where the latter method was more efficient for the extraction of phenolic compounds, with a significant percentage of effectiveness, the identification was performed by chromatography by HPLC/DAD, in which compounds were detected as gallic acid, parahydroxybenzoic acid, vanillic acid, caffeic acid, p-coumaric acid, feluric acid, feluric acid, parahydroxybenzoic acid, vanillic acid, caffeic acid, p-coumaric acid, feluric acid, para-hydroxybenzoic acid and p-coumaric acid, Vanillic acid, caffeic acid, p-coumaric acid, feluric acid, among others, the determination of the antioxidant activity was carried out by the decolorization of beta carotene, which decolorizes rapidly without the presence of an antioxidant, the application of phenolic compounds was carried out in fresh raw sausages and sausage products, where they were subjected to a sensory evaluation to see their possible acceptance, which allowed concluding that Citrus Sinensis peels have a high capacity to inhibit the oxidation of meat products.